Implementation of SAW Method in Scholarship Determination at YPN Medicom - Manullang, Jontinus; Situmorang, Sutrisno; Manik, Aditiarno; Huda, muhammad; Lubis, Harmoko (Jurnal ICT : Information and Communication Technologies, 2025)
To ease the burden of student tuition fees, AMIK Medicom provides a scholarship program. However, in the process of determining students who are entitled to receive scholarships, the institution experiences problems due to the large number of applicants, so that the selection process becomes ineffective and takes a long time. This research uses the Simple Additive Weighting (SAW) method as a solution to help the decision-making process. The SAW method was chosen because it is able to determine the best alternative from a number of candidates based on certain criteria, namely parents' income, number of children, number of dependents, place of residence, and academic grades. The results of the research show that this system is able to objectively rank students, making it easier for institutions to determine scholarship recipients more accurately and efficiently.